Exploring the Associations Between Patient Affect, Self-Care Actions, and Emergency Department Use for Community-Dwelling Adults. Issue 2 (April 2019) - Tzeng, Huey-Ming; Pierson, James Marcus; Kang, Yu; Barker, Anne; Yin, Chang-Yi
Abstract : Background: Nurses and other health care providers need to ensure that patients receive care that addresses their specific needs and wants. Purpose: This exploratory study examined the associations between patients' self-reported positive and negative affect, the perceived importance of 57 self-care actions, the desire and ability to perform them, and emergency department use in the past 3 months. Methods: A secondary analysis from a cross-sectional survey project that surveyed 250 community-dwelling adults living in the southern United States, 2015-2016. Independent t tests and the χ 2 test were used. Results: Positive affect was associated with positive perceptions of self-care actions and having no emergency department visit. Patients with a more negative affect perceived finding and using services that support their health behaviors as being important and expressed a desire to participate in local health screening or wellness events. Conclusions: Patients' perceptions of their self-care actions could lead to better outcomes. Abstract : Supplemental Digital Content is Available in the Text.